An Experimental Study on the Novel Ozone-Electro-Fenton Coupled Reactor for Treating Ofloxacin-Containing Industrial Wastewater - Han, Yifeng; Zhang, Lifen; Liu, Keyan; Tao, Jinliang; Wei, Feng (Water (Basel), 2025)
Industrial organic wastewater, with its complex composition, high biological toxicity, and recalcitrance, has become a major challenge in water pollution control. This is especially true for antibiotic-containing wastewater, such as ofloxacin wastewater, for which there is an urgent need to develop effective treatment technologies. Conventional treatment processes are insufficiently efficient, while individual advanced oxidation processes (AOPs) have drawbacks such as poor oxidation selectivity and catalyst deactivation. To address these issues, researchers have explored the coupling of different AOPs and found that such combinations can enhance the oxidation performance, achieve complementary advantages, reduce the equipment costs, and offer great development potential. An experiment was conducted to evaluate the performance of an Ozone-Electro-Fenton coupled process in treating ofloxacin industrial wastewater. The results demonstrated that under the same conditions, after four hours of treatment, the coupled process achieved a 70% reduction in the UV absorption peak of the wastewater, compared to less than 20% for individual processes, indicating a significant synergistic effect. Further optimization of the ozone aeration structure revealed that with a hole size of 0.5 mm, single-layer aeration holes, and six holes, the COD removal rate reached 96% after six hours, the ozone utilization improved to 85%, and the gas holdup stabilized at 4.6%. Under these conditions, the mixture of ozone and air bubbles formed mixed bubbles. Influenced by the electric field and electrode plate wall effects, the bubble residence time was prolonged. The bubble size was approximately 2.8 mm, the gas flow horizontal velocity was about 18.5 m/s, and after a horizontal displacement of 0.17 mm in the wastewater, the lateral velocity became zero. The ratio of the distance between the bubble center and the wall to the equivalent bubble diameter was approximately 3.45. The bubbles were subject to a strong wall effect, which extended their residence time. This not only facilitated the removal of small bubbles from the electrode plates but also enhanced the ion diffusion near the plates, thereby boosting pollutant degradation. This study shows that the Ozone-Electro-Fenton coupled process is highly effective in degrading ofloxacin industrial wastewater, offering an innovative solution for treating other antibiotic-containing wastewater. Future research will focus on further optimizing the process, improving its adaptability to complex matrix wastewater, and validating it at the pilot scale to promote its engineering application.